Excitation functions of (p,x) reactions on natural Nickel up to 40 MeV - Khandaker, Mayeen Uddin; Kim, G.; Kim, K.; Lee, M.; Kim, K.S. (Elsevier, 2011)
Production cross-sections of the residual radionuclides for the (nat)Ni(p,x)(55,56,57,58) m + (g)CO, (56,57)Ni nuclear reactions were measured up to 40 MeV by using a stacked-foil activation technique at the MC-50 cyclotron of the Korea Institute of Radiological and Medical Sciences. The results were compared with the reported experimental data as well as the theoretical calculations based on the TALYS and the ALICE-IPPE codes. The present results are in general good agreement with the other experimental data and calculated results. The integral yields for thick target were also deduced from the measured excitation functions of the produced radionuclides. The present experimental results will play an important role in enrichment of the literature data base for proton-induced reactions on natural nickel leading to various applications. (C) 2011 Elsevier BM. All rights reserved.